Serum creatinine levels to estimate kidney function in small-for-gestational age and appropriate-for-gestational age newborns - Indra Sandinirwan; Aris Primadi; Dany Hilmanto (Paediatrica Indonesiana, 2018)
Background The main parameter used to determine renal function in newborns is serum creatinine. Fetal growth restriction during pregnancy can cause the baby to be born small-for-gestational age. Serum creatinine levels in newborns are affected by muscle mass, gestational age, as well as the number of nephrons and kidney development. Objective To determine the usefulness of serum creatinine levels as an estimate of glomerular filtration rate in small-for-gestational age and appropriate-for-gestational age newborns. Methods This cross-sectional study was conducted in May-June 2018. The subjects were full term newborn infants consisting of small-for-gestational age and appropriate-for-gestational age groups (16 subjects each), born in Bandung City Regional Public Hospital. Serum creatinine level was tested by the Jaffe method. The estimated glomerular filtration rate was calculated based on serum creatinine, infant height, and a proportionality constant using the original Schwartz method, eGFR = [k * height]/SCr. Results Of 32 subjects, there were 17 spontaneous deliveries, 14 males, and 18 females. Mean serum creatinine levels in the small-for-gestational age and appropriate-for-gestational age groups were 0.94 (SD 0.36; 95%CI 0.75 to 1.14) mg/dL and 0.69 (SD 0.18; 95%CI 0.60 to 0.79) mg/dL (mean difference 0.25; 95%CI 0.05 to 0.46; P=0.009), respectively. The median estimated glomerular filtration rates (eGFR) in the small-for-gestational age and appropriate-for-gestational age groups were 25.69 mL/min/1.73m2 and 30.10 mL/min/1.73m2 (median difference 4.42; 95%CI 2.04 to 15.8; P=0.008), respectively. There was a weak negative correlation between serum creatinine and birth weight (r=-0.344; P=0.027). Conclusion Serum creatinine levels in small-for-gestational age newborns are significantly higher than in appropriate-for-gestational age newborns.